(untitled) (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The De Franceschi family owned a property and library in Gologorica, near Pazin. After the capitulation of Italy in 1943, they moved from Istria. Most of their books and archival material were transferred to the National and University Library, where they remained unprocessed and inaccessible to users for decades. The aim of this paper is to present the results of an analysis of data on previous ownership and dedications found in the Library of the De Franceschi family, recorded in the bibliographic descriptions during the cataloguing process, and to argue their importance in the context of preserving and valorising the cultural heritage of Istria. Approach/Methodology/Design. The analysis of provenance marks and inscriptions of the Library was preceded by extensive bibliographic processing and cataloguing of the materials in the Aleph library system. Data on provenance marks (ex libris and autographs) and inscriptions were entered in the bibliographic notes field. The field is searchable, which allows easy and quick data collection. Using the catalogue’s advanced search options, the Library’s material is selected by entering the location tag, PDF (Gift to De Franceshi), and typing the words ex libris, autograph or dedication in the note field. The data obtained in this way, repeated for each word, had to be further refined because there are also copies that are not from the De Franceschi Library. The collected quantitative data were further analysed qualitatively. Results. The Library contains 29 publications containing ex libris marks and 190 autographed publications. The De Franceschi family did not have their own ex libris but used an autograph to indicate provenance, usually in the form of C. De Franceschi. If we take into account the entire collection of the library, only slightly more than 9% of the books have this mark. Furthermore, there are 72 inscriptions in the library, often authored by the writers or editors of the donated works. Often there are several provenance marks on the book or a combination of provenance mark and inscriptions, which makes such an edition more interesting and valuable for bibliophiles. Limitations. The book material has been processed on several occasions. Systematic data entry for provenance marks and inscriptions was only implemented in the most recent and extensive phase. Practical implications. The value of recording data on ownership marks and dedications on books in the bibliographic description is presented and argued. Originality/value. While provenance marks and inscriptions have traditionally been documented for rare or old books, the research highlights the importance of recording these data for other types of material as well, especially for those associated with legacies.